Emergency nurses readiness towards providing emergency medical services - Nurumal, Mohd. Said; Shafie, Nur Fatin; Aung, Khin Thandar (Asian Academic Research Associates, 2017)
Emergency department act as a front line of any medical providers. One of the specialized areas under emergency is an emergency medical service (EMS). From the history in Malaysia about the development of the emergency medical services, nurses and physician have their own role in providing the care at the scene. However, the involvement of emergency nurses in providing EMS was limited. Today, EMS was manned by medical assistant compared to staff nurse. As been stated in the Emergency Nurses Association (ENA), the emergency nurses also need to be involved in providing EMS. It is important to know and explore their readiness when the nurses being ask to manned the EMS. The aim of this study was to explore the nurses' readiness in providing emergency medical services. A descriptive qualitative study design used and the data were collected and recorded from five emergency nurses by using a semi-structured interview based on inclusion and exclusion criteria. The data were analyzed using content analysis. From the analysis, one theme, inadequate exposure to emergency medical services (EMS) was emerged. This encompassed the permission was not given from the higher authority, lack of exposure to EMS, EMS was not highlighted among nurses, and assistant medical officers (AMO) were more knowledgeable. It was hard for nurses get the chance in providing EMS even though they were ready for it. Most of them were ready to join the EMS team if they have the chance and provided a positive response towards EMS. These findings may contribute to understanding the nurses’ perceptions and their challenges in providing EMS.